Nutritional assessments for ordinary medical care in patients with chronic liver disease. Issue 2 (25th July 2012) - Taniguchi, Eitaro; Kawaguchi, Takumi; Otsuka, Momoka; Uchida, Yuki; Nagamatsu, Ayu; Itou, Minoru; Oriishi, Tetsuharu; Ishii, Kumiko; Imanaga, Minami; Suetsugu, Takuro; Otsuyama, Jyuri; Ibi, Ryoko; et al.
<x xml:space="preserve">Abstract</x> Aim: In patients with chronic liver disease who are at risk of malnutrition, simple and useful assessments for nutritional status should be established for ordinary medical care. The prognostic nutritional index (PNI) and controlling nutritional status (CONUT) are simple assessments constructed of only two or three laboratory data. We aimed to describe the potential of PNI and CONUT as a nutritional assessment tool in patients with chronic liver disease. Methods: We enrolled 165 patients, aged 18–85 years, with chronic liver disease. These patients were nutritionally assessed by PNI or CONUT, demonstrating the association with the severity of chronic liver disease or anthropometric values. Results: The value of PNI or CONUT was significantly associated with the severity of chronic liver disease (P < 0.001, respectively). In addition, the value of CONUT was significantly associated with all the anthropometric values such as body mass index (BMI, P < 0.05), mid‐arm circumference (AC, P < 0.001), mid‐arm muscle circumference (AMC, P < 0.001), and triceps skinfold thickness (TSF, P < 0.001), whereas the value of PNI was significantly associated with the values of AC (P < 0.01), AMC (P < 0.05) and TSF (P < 0.05). Approximately 80% of cirrhotic patients were assessed by PNI or CONUT to have obvious malnutrition. Conclusion: PNI and CONUT are potential tools for nutritional assessment in patients with chronic liver disease, especially for ordinary medical care, because of their simplicity.